KINERJA DINAS KEBERSIHAN DALAM PENGELOLAAN SAMPAH DI KECAMATAN SANANA KABUPATEN KEPULAUAN SULA - Sukur Suleman; Karmila Ansar (JOURNAL OF ETHNIC DIVERSITY AND LOCAL WISDOM, 2021)
This study aims to understand, examine and describe the findings of researchers related to the performance of the Department of Cleanlinessin waste management in Sanana District, Sula Regency. This study uses a qualitative method with a descriptive approach. Data obtained throughobservation, interviews and documentation. The results showed that the performance of the Sanitation Department in waste management was notoptimal, this could be seen from the Work Productivity, Service Quality, Responsiveness, and Responsibility which started from the cleaning staff,the level of discipline, then the TPS and TPA to the level of empowerment of sola waste which was also minimal. carried out by the local government